Pengelolaan potensi pariwisata olahraga di Kabupaten Pati - Fajar Prasetyono (Journal of Physical Activity and Sports (JPAS), 2021)
This study aims to determine the level of management of the sports tourism potential in Pati Regency. The formulation of this research is, how is the management of sports tourism in Pati Regency? The purpose of this study was to determine the management of tourism potential in Pati Regency. This research uses descriptive qualitative research. The research location is in Pati Regency in an existing tourism area. The data source is in the form of primary data obtained directly from the research location through the interview and documentation stages as well as secondary data from records and laws. The data analysis used the triangulation method by drawing conclusions. The conclusion of this research is that the potential of sports tourism in Pati Regency is still partly not fully utilized. The suggestion from the researchers is that the local government should be more synergized with the community and private sector to increase awareness of the management of the potential for sports tourism, so that all parties can feel the positive impact of sports tourism in Pati Regency.